2019
DOI: 10.1186/s40359-019-0283-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pre-motivational factors on behavior via motivational factors: a test of the I-Change model

Abstract: Background The I-Change Model for explaining motivational and behavioral change postulates that an awareness phase precedes the motivation phase of a person, and that effects of pre-motivational factors on behavior are partially mediated by motivational factors. This study tests this assumption with regard to physical activity. Methods Observational longitudinal survey study (baseline, three months, six months) amongst Dutch adults ( N = 2434)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 53 publications
0
46
1
1
Order By: Relevance
“…Awareness factors such as knowledge, and motivational factors such as attitudes and selfefficacy are known to be precursors of an intention one has towards performing a behavior (45). It seemed that the intention to recruit patients of non-and low-recruiters was insufficiently grounded, as they showed poor study knowledge, few advantageous beliefs towards recruiting patients, and considerable recruitment barriers.…”
Section: Discussion Of Findings and Research Implications Evaluation mentioning
confidence: 99%
See 2 more Smart Citations
“…Awareness factors such as knowledge, and motivational factors such as attitudes and selfefficacy are known to be precursors of an intention one has towards performing a behavior (45). It seemed that the intention to recruit patients of non-and low-recruiters was insufficiently grounded, as they showed poor study knowledge, few advantageous beliefs towards recruiting patients, and considerable recruitment barriers.…”
Section: Discussion Of Findings and Research Implications Evaluation mentioning
confidence: 99%
“…However, the theory less explicitly dedicates attention to the determinants preceding the formation of motivation. Research has, for instance, shown that factors such as knowledge and risk perceptions may play an important role as factors determining motivational factors such as attitudes and self-efficacy (45). Additionally, only a limited amount of the variance of behavior is explained by intention, and therefore the role of developing and enacting action plans should be addressed in order to understand and change behavior (46)(47)(48)(49)(50).…”
Section: Understanding Adherence To Healthy Lifestyle and Medical Behmentioning
confidence: 99%
See 1 more Smart Citation
“…an accurate perception) of one's own behaviour (Eggers et al, 2016;de Vries, 2017). Behavioural cognizance concerns the level of a person's awareness about his or her own health behaviour (Kasten, van Osch, Candel, & de Vries, 2019). If a person is aware of the problem, the associated health risks and their (lack of) health behaviour (e.g.…”
Section: Pre-motivational Determinants Of Drinking Behaviourmentioning
confidence: 99%
“…not engaging in BD), a person will be more motivated to process information about motivational factors (Eggers et al, 2016). Therefore, adolescents need to know the effects of alcohol in order to become aware of the negative effects and the role of their own drinking behaviour (Jander et al, 2013;Kasten et al, 2019). Furthermore, some studies suggest that levels of adolescents' knowledge about what BD is and causes may be suboptimal (Botvin, Griffin, Diaz, & Ifill-Williams, 2001;Jander et al 2013).…”
Section: Pre-motivational Determinants Of Drinking Behaviourmentioning
confidence: 99%